Análise descritiva dos principais produtos notificados no sistema nacional de notificações para a vigilância sanitária (NOTIVISA) - Cleber Massato Toda; Cleber Massato Toda; Jessica Natalia Andre (EaD & Tecnologias Digitais na Educação, 2017)
The Rational Use of Medicines (RDU) should be encouraged as a way to ensure efficacy and safety. Despite all the care and the RDU, denote the eminence of Adverse Drug Reactions (ADR). The National Health Surveillance Agency as a way to soften the appearance of the ADR created the National Reporting System for Sanitary Surveillance (NOTIVISA). This article aims to identify the main products were reported in NOTIVISA related adverse events (AE), complaints-techniques (QT) and poisonings. It is a descriptive and retrospective study conducted by analyzing the reports provided by NOTIVISA, for the period 2007 to 2012 In the results, there was a high increase in notifications of EA and QT primarily by the drugs. Therefore, it is critical that urgent measures in order to reverse this situation.